2014
DOI: 10.3389/fpsyg.2014.01391
|View full text |Cite
|
Sign up to set email alerts
|

Mental imagery interventions reduce subsequent food intake only when self-regulatory resources are available

Abstract: Research has shown that imagining food consumption leads to food-specific habituation effects. In the present research, we replicated these effects and further examined whether the depletion of self-regulatory resources would reduce the habituation effects of imagined food consumption. Since self-regulatory resources have been shown to reduce habituation effects during the perception of emotional stimuli, we expected a reduction in habituation effects from imagined food consumption when self-regulatory resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 63 publications
3
30
0
Order By: Relevance
“…Likewise, systematic reviews and meta-analyses of randomized controlled trials have been reported on the effects of imagery in the performance of motor, strength, and cognitive tasks, 5 as a way to alter pain perceptions, 6 its use by nursing practitioners for symptom management, 7 and as part of other psychosocial treatments for depression and anxiety among cancer patients. 8 More recently, researchers have shown that guided mental imagery can help individuals increase physical activity, 9,10 modify food consumption and cravings, 1113 and cope with stress. 14,15 Finally, neuroscientists have also extensively studied the cognitive processes associated with imagery for problem solving, speech, motor function, and memory.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, systematic reviews and meta-analyses of randomized controlled trials have been reported on the effects of imagery in the performance of motor, strength, and cognitive tasks, 5 as a way to alter pain perceptions, 6 its use by nursing practitioners for symptom management, 7 and as part of other psychosocial treatments for depression and anxiety among cancer patients. 8 More recently, researchers have shown that guided mental imagery can help individuals increase physical activity, 9,10 modify food consumption and cravings, 1113 and cope with stress. 14,15 Finally, neuroscientists have also extensively studied the cognitive processes associated with imagery for problem solving, speech, motor function, and memory.…”
Section: Introductionmentioning
confidence: 99%
“…This task has previously shown to be an effective intervention to deplete self-regulatory resources (Missbach, Florack, Weissmann, & König, 2014). Participants in the high self-regulatory depletion condition had to count backwards from 500 in multiple steps of seven while standing on one leg.…”
Section: Depletion Taskmentioning
confidence: 98%
“…And indeed, research on inhibitory control in the area of eating behavior suggests that such intrusive thoughts ought to be deliberately suppressed (Anderson and Bjork, 1994), inhibiting retrieval of food-related information from memory (Davidson et al, 2005) in order to prevent consumption in situations when it is undesirable. Interestingly, recent research found that multiple repetitions of these “consumption” thoughts not only halt further increases in the desire to eat the food but also decrease the desire and reduce actual consumption of a specific food that participants imagined themselves eating (Morewedge et al, 2010; Missbach et al, 2014). This “paradoxical” decrease of consumption desire after its repeated rehearsal has been suggested to reflect habituation effects (Morewedge et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Only after repeated presentations, when the food stimulus matches the previously stored information in memory, does the processing of the food stimulus, along with the responsiveness to it, decrease (Epstein et al, 2009). Research has demonstrated habituation effects across different types of responses such as salivation, motivated responding, and food intake, and with different food types such as cheeseburgers, cheese, M&Ms, gummy bears, and walnuts (Epstein et al, 2003; Morewedge et al, 2010; Missbach et al, 2014). Habituation was also found across different types of paradigms such as repeated exposure to actual food stimuli (e.g., Epstein et al, 2003, 2009) and repeated imagined consumption of a particular food (Morewedge et al, 2010; Missbach et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation